The Role of Mutation Induction Technology in Forage Breeding - Achmad Fanindi; Harmini Harmini (Indonesian Center for Animal Research and Development, 2021)
Mutation induction in breeding is one of many ways to improve the character of a plant, including forage crops. Formation of new variety of forage plants, especially grass is still very rare in Indonesia due to several obstacles, including the flower structure, ploid and reproductive systems of forage plants. Mutation induction in breeding as a method of producing new varieties of forage plants (grass and legume) can be utilized by eliminating the constraints in forage plants, because it can create new variety without being restricted by floral structure and reproductive system of plant. The paper aims to describe the mutation breeding and its methods on forage plants and its prospect to obtain new varieties of superior forage plants to meet the needs of forage in Indonesia. A number of factors, including mutation technique, mutagenic type, seed and other factors, are determining the success of mutational breeding. The creation of new types of forage plants by mutation-induction is aiming to increase productivity, improve forage performances and resist abiotic and biotic stress. Mutation breeding is expected to produce new varieties of superior forage plants in a relatively shorter time, because forage plants can be propagated in a vegetative or generative manner. It is epxected that the assembly of new varieties of forage plants can meet the needs of forage in quantity and quality.